2012
DOI: 10.5455/medarh.2012.66.41-44
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Prostate Volume, Prostate Specific Antigen Density and Number of Biopsy Samples on Prostate Cancer Detection

Abstract: A im: Establish the main differences in the prostate volume, prostate specific antigen density (PSAD), number of biopsy samples in patients with primarily or rebiopsy detected prostate cancer. Materials and methods: In the 2007-2009 period, at the KCUS Urology Clinic, there were 379 TRUS guided prostate biopsies in 323 patients with known prostate volume. The total of 56 patients (17.3%) underwent the first rebiopsy, primarily due to precancerous lesions. The mean prostate volume, ranges of prostate size, PSAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Aganovic et al were found higher PSA density is related to a higher Gleason score and it supports the results. 13…”
Section: Resultsmentioning
confidence: 99%
“…Aganovic et al were found higher PSA density is related to a higher Gleason score and it supports the results. 13…”
Section: Resultsmentioning
confidence: 99%
“…However, it indicates that in our study a change in the number of taken cores (targeted) should not significantly affect the results obtained. There are scientific publications on the impact of the number of collected cores on the detection of prostate cancer, it has been shown that their increase correlates with the improvement in detection [ 14 , 15 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The adequate sampling number has not yet been determined. Aganovic et al [ 20 ] reported that a higher number of biopsy samples (mean, 14.1 vs. 10.9 with initially detected cancer) was related to a higher chance of cancer detection with repeat biopsy [ 20 ]. Since the rebiopsy group showed a larger prostate volume with a lower tumor burden, targeting more than the 12-core routine biopsy might be recommendable.…”
Section: Discussionmentioning
confidence: 99%